Multitracer Molecular Imaging of Paget Disease Targeting Bone Remodeling, Fatty Acid Metabolism, and PSMA Expression on PET/CT. (December 2016) - Derlin, Thorsten; Weiberg, Desiree; Sohns, Jan M.
Abstract : Abstract: Paget disease is a chronic disorder resulting in enlarged and misshapen bones, and is caused by disorganized bone remodeling. We present the case of an 85-year-old man with prostatic adenocarcinoma and known Paget disease of the right iliac bone who underwent 68 Ga–prostate-specific membrane antigen ligand, 11 C-acetate, and 18 F-fluoride PET/CT for restaging of cancer. On all PET scans, increased tracer accumulation was observed in Paget disease of bone. Besides that Paget disease may mimic metastases on PET/CT using various radiotracers, including 68 Ga–prostate-specific membrane antigen ligands and 11 C-acetate, this case highlights the potential of multiparametric disease characterization on PET.